An Implementation Roadmap for Establishing Remote Infectious Disease Specialist Support for Consultation and Antibiotic Stewardship in Resource-Limited Settings. (16th December 2022) - Livorsi, Daniel J; Abdel-Massih, Rima; Crnich, Christopher J; Dodds-Ashley, Elizabeth S; Evans, Charlesnika T; Goedken, Cassie Cunningham; Echevarria, Kelly L; Kelly, Allison A; Spires, S Shaefer; Veillette, John J; Vento, Todd J; Jump, Robin L P
Abstract: Infectious Disease (ID)–trained specialists, defined as ID pharmacists and ID physicians, improve hospital care by providing consultations to patients with complicated infections and by leading programs that monitor and improve antibiotic prescribing. However, many hospitals and nursing homes lack access to ID specialists. Telehealth is an effective tool to deliver ID specialist expertise to resource-limited settings. Telehealth services are most useful when they are adapted to meet the needs and resources of the local setting. In this step-by-step guide, we describe how a tailored telehealth program can be implemented to provide remote ID specialist support for direct patient consultation and to support local antibiotic stewardship activities. We outline 3 major phases of putting a telehealth program into effect: pre-implementation, implementation, and sustainment. To increase the likelihood of success, we recommend actively involving local leadership and other stakeholders in all aspects of developing, implementing, measuring, and refining programmatic activities. Abstract : Telehealth is an effective tool for sharing Infectious Disease specialist expertise with resource-limited settings. In this step-by-step guide, we outline how a telehealth program can be implemented to provide remote ID specialist support for patient consultation and/or antibiotic stewardship.